1984
DOI: 10.1002/fld.1650040207
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental solutions and numerical methods for flow problems

Abstract: SUMMARYAn approach for the numerical solution of flow problems based on the concept o f fundamental solutions of differential equations is described. This approach uses the finite element methodology but does not rely on the concept of variational principle or that of residuals. Thc approach is shown to be well-suited for many typcs of flow problems. Various applications of this approach are discussed in this paper, with particular emphasis placed on the solution of potential flows and viscous flows containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In Ref. (165), it has been shown that the solid boundary vorticity values can be determined through the kinematic relationship between the instantaneous velocity and vorticity fields. It should be noted that the kinematic relationship, Equation (B2), is valid in both the solid region S and the fluid region R. Therefore, the vorticity field throughout S and R must be such that the velocity in S as computed by Equation (B2) should agree with the prescribed solid body motion.…”
Section: B1 Velocity-vorticity Formulationmentioning
confidence: 99%
“…In Ref. (165), it has been shown that the solid boundary vorticity values can be determined through the kinematic relationship between the instantaneous velocity and vorticity fields. It should be noted that the kinematic relationship, Equation (B2), is valid in both the solid region S and the fluid region R. Therefore, the vorticity field throughout S and R must be such that the velocity in S as computed by Equation (B2) should agree with the prescribed solid body motion.…”
Section: B1 Velocity-vorticity Formulationmentioning
confidence: 99%
“…(1) and (2). Detailed numerical procedures are described in Sohn (1986), who developed a numerical method of solving the time-dependent incompressible Navier-Stokes equations in the integro-differential formulation based on Wu (1984). The reliability and accuracy of the numerical method has been ascertained.…”
Section: Boundary Conditions and Discretization Of The Governing Equamentioning
confidence: 99%
“…The velocity corrections which were obtained from BIE (25) may be analogously compared with the ones obtained from (7), where the pressure derivatives were determined by an alternative differencing (usually, velocity derivatives) of the pressure corrections from (23).…”
Section: Velocity Corrections As the Equalitymentioning
confidence: 99%